Improvement of plastic roll change process on primary packing machine using lean and six sigma approaches - Zulazha Bin Sehak (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Continuous improvement process is a tradition of method improvement focusing the elimination of wast in all systems and process in an organisation. Continuous improvement has been an important part of manufacturing history since the humans are always looking for a better way to do their jobs or improve their tools. The current problem happened are the operator need to change the plastic roll average in a day about 3.667 times in operation hour and each time of change take about 3 minute.